2023
DOI: 10.1177/01902725231196851
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Skin Red and Yellow Undertone: Reliability of Ratings and Predicted Relevance for Social Experiences

Amelia R. Branigan,
Johanna G. Nunez,
Mariya Adnan Khan
et al.

Abstract: It is well established that skin lightness-darkness is associated with social outcomes, but little is known regarding the social salience of skin undertones (redness and yellowness). Our study addresses two related research questions on this topic: first, we ask whether red and yellow undertones are consistently perceived by observers; second, we ask whether red and yellow undertones are associated with expectations of discrimination across a range of social settings. We address these questions using novel sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Consistent with the university's designation as an Asian American Native American Pacific Islander and Hispanic Serving Institution, the majority of study participants identified as Asian (54%) and about one-fifth each identified as Latinx (23%) and White (18%); 3% each identified as Black and Other race-ethnicities (see Table 1). Over two-thirds of participants identified as Cisgender Woman (71%), over one-quarter as Cisgender Man (27%); two Branigan et al (2023) drew upon prior theory and research to conceptualize the importance of undertone for colorism research. Skin redness and yellowness, for instance, can be perceived as signals of attractiveness and health, although these colors' momentary fluctuations due to emotions, diet, and sleep may mean that their social signaling is less stable than is skin's darkness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the university's designation as an Asian American Native American Pacific Islander and Hispanic Serving Institution, the majority of study participants identified as Asian (54%) and about one-fifth each identified as Latinx (23%) and White (18%); 3% each identified as Black and Other race-ethnicities (see Table 1). Over two-thirds of participants identified as Cisgender Woman (71%), over one-quarter as Cisgender Man (27%); two Branigan et al (2023) drew upon prior theory and research to conceptualize the importance of undertone for colorism research. Skin redness and yellowness, for instance, can be perceived as signals of attractiveness and health, although these colors' momentary fluctuations due to emotions, diet, and sleep may mean that their social signaling is less stable than is skin's darkness.…”
Section: Methodsmentioning
confidence: 99%
“…See also: https://nis.princeton.edu/ downloads/nis-skin-color-scale.pdf; https://www.loreal.com/en/articles/science-and-technology/expert-inskin/ skin undertone (redness, yellowness) is important given skin undertone has been less studied than skin darkness. Adding to a recent study examining undertone in photographs (Branigan et al 2023) 1 , we compared in-person human ratings of undertone to handheld device readings of redness and yellowness. The current study also extends prior results by using a specialized room with equalized conditions such as lighting.…”
Section: Introductionmentioning
confidence: 99%